EBV-associated diseases: Current therapeutics and emerging technologies - Chakravorty, Srishti; Afzali, Behdad; Kazemian, Majid (Frontiers in Immunology, 2022)
EBV is a prevalent virus, infecting >90% of the world’s population. This is an oncogenic virus that causes ~200,000 cancer-related deaths annually. It is, in addition, a significant contributor to the burden of autoimmune diseases. Thus, EBV represents a significant public health burden. Upon infection, EBV remains dormant in host cells for long periods of time. However, the presence or episodic reactivation of the virus increases the risk of transforming healthy cells to malignant cells that routinely escape host immune surveillance or of producing pathogenic autoantibodies. Cancers caused by EBV display distinct molecular behaviors compared to those of the same tissue type that are not caused by EBV, presenting opportunities for targeted treatments. Despite some encouraging results from exploration of vaccines, antiviral agents and immune- and cell-based treatments, the efficacy and safety of most therapeutics remain unclear. Here, we provide an up-to-date review focusing on underlying immune and environmental mechanisms, current therapeutics and vaccines, animal models and emerging technologies to study EBV-associated diseases that may help provide insights for the development of novel effective treatments.